2017
DOI: 10.1111/joor.12539
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of oro‐facial pain – health technology assessment including a systematic review with network meta‐analysis

Abstract: This health technology assessment evaluated the efficacy of pharmacological treatment in patients with oro-facial pain. Randomised controlled trials were included if they reported pharmacological treatment in patients ≥18 years with chronic (≥3 months) oro-facial pain. Patients were divided into subgroups: TMD-muscle [temporomandibular disorders (TMD) mainly associated with myalgia]; TMD-joint (TMD mainly associated with temporomandibular joint pain); and burning mouth syndrome (BMS). The primary outcome was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 174 publications
4
70
0
5
Order By: Relevance
“…Other recent research into treatment options for the management of TMD has included orthognathic surgery, 49 TMJ lavage, 50 physiotherapy, 51,52 low-level laser therapy, 53,54 exercise therapy, 55 pharmacological treatment, 56 and acupuncture. 57 However, results are mixed and generally unconvincing.…”
Section: Alternative Treatment Options For Tmdmentioning
confidence: 99%
“…Other recent research into treatment options for the management of TMD has included orthognathic surgery, 49 TMJ lavage, 50 physiotherapy, 51,52 low-level laser therapy, 53,54 exercise therapy, 55 pharmacological treatment, 56 and acupuncture. 57 However, results are mixed and generally unconvincing.…”
Section: Alternative Treatment Options For Tmdmentioning
confidence: 99%
“…A recent network meta‐analysis of pharmacological management of BMS pain indicated that capsaicin had beneficial effects . Topical capsaicin is indeed an aetiological treatment option .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment is frequently recommended for orofacial pain 42 ; however, we found only 6 (18%) RTCs using pharmacological treatments for TMD. Most of the existing literature evaluating pharmacologic treatments are observational clinical studies instead of RCTs 40,59 .…”
Section: Discussionmentioning
confidence: 63%
“…The most commonly used drugs to decrease pain and inflammatory process in joints and/or muscles are myorelaxants, non-steroidal anti-inflammatory drugs (NSAIDs), analgesics, tricyclic antidepressants (TCAs), benzodiazepines, and corticosteroids 9,39,41 . A wide range of pharmacotherapeutic agents is available; however, there is a lack of scientific evidence and no conclusive result for any of these drugs for the TMD population 6,10,39,42 .…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%